Regulation of photoperiodic flowering by Arabidopsis photoreceptors - Mockler, Todd (The National Academy of Sciences, 2003)
Photoperiodism is a day-length-dependent seasonal change of physiological or developmental activities that is widely found in plants and animals. Photoperiodic flowering in plants is regulated by photosensory receptors including the red/far-red light-receptor phytochromes and the blue/UV-A light-receptor cryptochromes. However, the molecular mechanisms underlying the specific roles of individual photoreceptors have remained poorly understood. Here, we report a study of the day-length-dependent response of cryptochrome 2 (cry2) and phytochrome A (phyA) and their role as day-length sensors in Arabidopsis. The protein abundance of cry2 and phyA showed a diurnal rhythm in plants grown in short-day but not in plants grown in long-day. The short-day-specific diurnal rhythm of cry2 is determined primarily by blue light-dependent cry2 turnover. Consistent with a proposition that cry2 and phyA are the major day-length sensors in Arabidopsis, we show that phyA mediates far-red light promotion of flowering with modes of action similar to that of cry2. Based on these results and a finding that the photoperiodic responsiveness of plants depends on light quality, a model is proposed to explain how individual phytochromes and cryptochromes work together to confer photoperiodic responsiveness in Arabidopsis.